2020
DOI: 10.1007/s00420-020-01532-7
|View full text |Cite
|
Sign up to set email alerts
|

Secondary prevention of UV-induced skin cancer: development and pilot testing of an educational patient counseling approach for individual sun protection as standard procedure of patient care

Abstract: Objective To outline the development and pilot testing of a patient counseling approach for individual sun protection for patients in outdoor professions diagnosed with squamous cell carcinoma or multiple actinic keratosis due to solar UV radiation. This is a secondary prevention measure as part of the standard procedure of patient care by the respective statutory accident insurance. Methods Results of guideline-based qualitative interviews with seven outdoor workers and a search of literature formed the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In this study, it was also demonstrated that, despite a high level of interest in enhanced sun protection behavior across specific occupational groups, the special needs of outdoor workers are rarely considered in Germany [38]. This correlates with current recommendations to prospectively address the unmet needs of NMSC patients (Table 2), especially that employers should use technology to track solar UVR exposure in the workplace, establish cost-effective strategies for sun-safe behavior, and ensure that outdoor workers are getting regular skin cancer screenings, and that patient advocacy organizations, doctors, and other healthcare professionals, as well as employers, should collaborate to improve skin cancer prevention and sun-safe workplace conditions [1].…”
Section: Photoprotection As a Standard In Outdoor Workersmentioning
confidence: 80%
See 2 more Smart Citations
“…In this study, it was also demonstrated that, despite a high level of interest in enhanced sun protection behavior across specific occupational groups, the special needs of outdoor workers are rarely considered in Germany [38]. This correlates with current recommendations to prospectively address the unmet needs of NMSC patients (Table 2), especially that employers should use technology to track solar UVR exposure in the workplace, establish cost-effective strategies for sun-safe behavior, and ensure that outdoor workers are getting regular skin cancer screenings, and that patient advocacy organizations, doctors, and other healthcare professionals, as well as employers, should collaborate to improve skin cancer prevention and sun-safe workplace conditions [1].…”
Section: Photoprotection As a Standard In Outdoor Workersmentioning
confidence: 80%
“…In a recent study from Germany, a patient counseling method for customized sun protection was developed and pilot tested for individuals in outdoor professions diagnosed with squamous cell carcinoma or multiple actinic keratosis due to solar UVR [38]. The 'counseling approach for individual sun protection' comprised seven general and eight add-on modules that can be combined and tailored to the patient's specific needs-interactive, educational components (e.g.…”
Section: Photoprotection As a Standard In Outdoor Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the PRISMA flow diagram of the selection criteria. A total of 1398 studies were screened, and 249 studies (17.8%) were ultimately included in the database …”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been reported that the vast majority of professions with time spent outdoors for more than 1 hour are at particular risk [22]. It also was discovered that the unique needs of outdoor workers are rarely considered while developing preventative measures [23]. Different preventative measures are displayed in Table 1.…”
Section: Introductionmentioning
confidence: 99%